Representación de la Comunidad LGBTI en el discurso de los Medios Impresos de Riobamba. Año 2020. - Baldeon Araujo, Ricardo Xavier (2022)
This research work addresses the representation of the LGBTI community in the discourse used in the print media Los Andes and La Prensa de Riobamba, year 2020, taking into account that the representation of this group has been affected by various violations of their rights, discrimination or stereotypes generated by the lack of education and the non-use of appropriate language. Within this, the main objective is to analyze the representation of the LGTBI community in the discourse of the printed media of Riobamba in 2020. In order to fulfill the objectives, a qualitative-quantitative methodology was used, which allowed an analysis and, in turn, the respective interpretation, applying interviews to specialists of the LGBTI community, in addition to the information collected through the bibliographic search of primary and secondary sources, taking the Frankfurt school and its critical theory and with the interviews conducted to understand the discourse in the print media. The research process allowed us to discover how the messages have been constructed in the different print media of Riobamba and with the results we made a communicational product, consisting of 5 short videos for the TIK TOK platform, where the theme of the representation of the LGBTI community is addressed.